Temperatura dos animais - Côdo, Vitório (Revista Ceres, 1950)
In this article the author emphasizes the advantage of determining the temperature of the domestic animals, since the raise of temperature is an indication of any infectious disease. He describes how the animals should be examined, what should be done before and during the examination and considers the importance of the excitation upon the raise of the temperature. Finally it is shown on tables the mean temperature of the domestic animals and discussed the meaning of hypothermy.